The determination of wages of newly hired employees: survey evidence on internal versus external factors - Kamil Galuščák; Mary Keeney; Daphne Nicolitsas; Frank Smets; Pawel Strzelecki; Matija Vodopivec (European Central Bank (ECB), 2010)
This paper uses information from a rich firm-level survey on wage and price-setting procedures, in around 15,000 firms in 15 European Union countries, to investigate the relative importance of internal versus external factors in the setting of wages of newly hired workers. The evidence suggests that external labour market conditions are less important than internal pay structures in determining hiring pay, with internal pay structures binding even more often when there is labour market slack. When explaining their choice firms allude to fairness considerations and the need to prevent a potential negative impact on effort. Despite the lower importance of external factors in all countries there is significant cross-country variation in this respect. Cross-country differences are found to depend on institutional factors (bargaining structures); countries in which collective agreements are more prevalent and collective agreement coverage is higher report to a greater extent internal pay structures as the main determinant of hiring pay. Within-country differences are found to depend on firm and workforce characteristics; there is a strong association between the use of external factors in hiring pay, on the one hand, and skills (positive) and tenure (negative) on the other.
Keywords: J31; J41; 330; business cycle; employee turnover; internal pay structure; newly hired workers; survey data; wage rigidity; Lohnrigidität; Lohnstruktur; Humankapital; Arbeitsmobilität; EU-Staaten